RIP-seq reveals RNAs that interact with RNA polymerase and primary sigma factors in bacteria - Vaňková Hausnerová, Viola; Shoman, Mahmoud; Kumar, Dilip; Schwarz, Marek; Modrák, Martin; Jirát Matějčková, Jitka; Mikesková, Eliška; Neva, Silvia; Herrmannová, Anna; Šiková, Michaela; Halada, Petr; Novotná, Iva; et al. (Nucleic acids research, 2024)
Bacteria have evolved structured RNAs that can associate with RNA polymerase (RNAP). Two of them have been known so far-6S RNA and Ms1 RNA but it is unclear if any other types of RNAs binding to RNAP exist in bacteria. To identify all RNAs interacting with RNAP and the primary σ factors, we have established and performed native RIP-seq in Bacillus subtilis, Corynebacterium glutamicum, Streptomyces coelicolor, Mycobacterium smegmatis and the pathogenic Mycobacterium tuberculosis. Besides known 6S RNAs in B. subtilis and Ms1 in M. smegmatis, we detected MTS2823, a homologue of Ms1, on RNAP in M. tuberculosis. In C. glutamicum, we discovered novel types of structured RNAs that associate with RNAP. Furthermore, we identified other species-specific RNAs including full-length mRNAs, revealing a previously unknown landscape of RNAs interacting with the bacterial transcription machinery.
Keywords: genetická transkripce; Streptomyces coelicolor; Mycobacterium smegmatis; Bacillus subtilis; DNA-Directed RNA Polymerases; sigma faktor; Transcription, Genetic; Sigma Factor; bakteriální RNA; nekódující RNA; bakteriální proteiny; regulace genové exprese u bakterií; RNA, Untranslated; Corynebacterium glutamicum; Mycobacterium tuberculosis; konformace nukleové kyseliny; Gene Expression Regulation, Bacterial; Bacterial Proteins; Nucleic Acid Conformation; RNA, Bacterial; DNA řízené RNA-polymerasy